Unidade de ensino potencialmente significativa para o ensino das operações fundamentais com números naturais - Souza, Paula Oliveira de (2024)
This dissertation examines the impacts of teaching through a Potentially Significant Teaching Unit (UEPS), incorporating the use of games as a tool to promote meaningful learning of operations with natural numbers, in a 6th year elementary school class. The challenge that motivated the investigation is based on the observation and review of studies on the difficulty in the teaching and learning process of the four operations, mainly in Elementary Education, suggesting the importance of proposing methodological alternatives. In this way, support is sought in the Theory of Meaningful Learning, recommended by David Paul Ausubel, to answer the following question: What are the potential of a didactic sequence in the format of a UEPS in promoting meaningful understanding of operations with natural numbers? Thus, a UEPS was created suggesting the integration of mathematical games as essential complementary resources in the teaching-learning process, since this approach can awaken students' interest in everyday mathematical challenges, correlating them with skills and abilities developed in the context of operations with natural numbers, which include reading, writing, understanding the decimal number system and problem solving. Therefore, the study seeks to analyze the potential of a teaching sequence structured as UEPS for the effective understanding of mathematical operations. This UEPS was implemented with students in the 6th year of Elementary School at Colégio Tiradentes da Police Militar III, in Ariquemes-RO. The investigation is characterized as qualitative action research, using records from the researcher's logbook, evaluation and descriptive observation as data collection instruments. Data were analyzed during and after the implementation of each step of the UEPS. The results demonstrate that the UEPS is capable of offering situations to promote meaningful learning, as it makes it possible to identify underlying concepts, promotes progressive differentiation, integrative reconciliation and encourages students to apply the concepts studied in new contexts. The study originated the educational product entitled Mathematics: a UEPS for the development of skills in the four operations through games, as a support resource for Mathematics teachers, available on the Science and Mathematics Teaching Program page of the University of Passo Fundo in http://ppgecm.upf.br/, on the specific page of educational products produced in the program at https://www.upf.br/produtoseducacionais/ and on the EduCapes page at http://educapes.capes.gov.br /handle/capes/742944.